Genital use of talc and risk of ovarian cancer: a meta-analysis. Issue 3 (May 2018) - Berge, Wera; Mundt, Kenneth; Luu, Hung; Boffetta, Paolo
Abstract : Some epidemiological studies suggest an association between genital use of talc powders and increased risk of ovarian cancer, but the evidence is not consistent. We performed a meta-analysis of epidemiological studies to formally evaluate this suspected association. A systematic search was conducted in Medline, Embase, and Scopus, leading to the identification of 24 case–control studies and three cohort studies. In the meta-analysis, we used a random-effect model to calculate summary estimates of the association between genital use of talc and occurrence of ovarian cancer. We assessed potential sources of between-study heterogeneity and presence of publication bias. The summary relative risk (RR) for ever use of genital talc and ovarian cancer was 1.22 [95% confidence interval (CI): 1.13–1.30]. The RR for case–control studies was 1.26 (95% CI: 1.17–1.35) and for cohort studies was 1.02 (95% CI: 0.85–1.20, P heterogeneity =0.007). Serous carcinoma was the only histologic type for which an association was detected (RR: 1.24; 95% CI: 1.15–1.34). There was a weak trend in RR with duration and frequency of genital talc use. This meta-analysis resulted in a weak but statistically significant association between genital use of talc and ovarian cancer, which appears to be limited to serous carcinoma with suggestion of dose-response. The heterogeneity of results by study design however, detracts from a causal interpretation of this association. Abstract : Supplemental Digital Content is available in the text.